How to Be an Anticapitalist in the Twenty-First Century - Wright, Erik Olin (London Verso, 2019)
What is wrong with capitalism, and how can we change it? Capitalism has transformed the world and increased our productivity, but at the cost of enormous human suffering. Our shared values--equality and fairness, democracy and freedom, community and solidarity--can provide both the basis for a critique of capitalism and help to guide us toward a socialist and democratic society. Erik Olin Wright has distilled decades of work into this concise and tightly argued manifesto: analyzing the varieties of anticapitalism, assessing different strategic approaches, and laying the foundations for a society dedicated to human flourishing. How to Be an Anticapitalist in the Twenty-First Century is an urgent and powerful argument for socialism, and an unparalleled guide to help us get there. Another world is possible. Included is an afterword by the author's close friend and collaborator Michael Burawoy.--
Keywords: Anti-globalization movement -- Capitalism